An Empirical Analysis of Sustainable Agricultural Finance Adoption among South Indian Farmers - Antony Francis; Jerome. S; Amit Kumar Nag (Forum Kerjasama Pendidikan Tinggi, 2026)
Sustainable agricultural finance has become an important mechanism for promoting climate-resilient agriculture and supporting the long-term sustainability of farming systems. Despite its growing importance, the adoption of sustainable financial products among farmers remains uneven, particularly in developing regions where institutional, technological and financial constraints continue to shape investment decisions. This study examines the determinants of sustainable agricultural finance adoption among farmers in Kerala, Karnataka and Tamil Nadu by analysing the influence of financial literacy, climate risk awareness, digital readiness and institutional support. A quantitative cross-sectional survey was conducted among 438 farmers using a structured questionnaire. The collected data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings show that all four determinants significantly influence sustainable agricultural finance adoption. Institutional support emerged as the strongest predictor (β = 0.312), followed by digital readiness (β = 0.241), financial literacy (β = 0.218) and climate risk awareness (β = 0.186). The proposed model demonstrated satisfactory explanatory power (R² = 0.524), strong predictive relevance (Q² = 0.391) and good model fit (SRMR = 0.067; NFI = 0.914). The findings indicate that strengthening institutional mechanisms, expanding digital financial infrastructure, improving financial literacy and increasing climate risk awareness are essential for encouraging sustainable agricultural finance adoption. The study adds to the growing literature on sustainable agricultural finance by providing empirical evidence from South India and offers practical guidance for policymakers, financial institutions and agricultural development agencies seeking to strengthen sustainable financial systems and promote resilient agricultural development.